RFID design principles - Lehpamer, Harvey (Artech House, 2012)
RFID (radio-frequency identification) is an emerging communication system technology and one of the most rapidly growing segments of today's automatic identification data collection industry. This book offers professionals a detailed understanding of RFID design essentials, key applications, and important management issues.